A case of hypereosinophilia with digital ischaemia successfully treated with intravenous prostaglandin E1 - M. Kaga; H. Takeuchi; K. Iwahara; H. Ihara (Wiley, 2021)
Abstract In the therapeutic management of eosinophilic disorder, it is important to prevent hypereosinophilia (HE)‐related organ damage even in the process of diagnosis. We describe here a unique clinical and histopathological findings of the patient with HE accompanied with digital ischaemia. Treatment with intravenous prostaglandin E1 was essential for digital ischaemia in our case while benralizumab, humanized monoclonal antibody against interleukin‐5 receptorα, did not affect. Our case suggests an earlier intervention for digital ischaemia in the therapeutic management of eosiniphilic disorder.